Silicon photomultipliers for visible light communications - Ahmed, Z (2022)
Over the past decade, avalanche photodiodes (APDs) have been widely investigated for visible light communications. However, the gain and collection area of an APD is limited, which prevents this type of detector from improving its sensitivity. The gain is typically limited by excess noise, and its overall capacitance limits the collection area. Typically, the APDs of less than a square millimetre only have a bandwidth of more than 100 MHz. The excess noise factor can be avoided by biasing an APD above its breakdown voltage, significantly increasing its gain. The high gain makes an APD sensitive enough to detect photons down to a single photon, hence referred to as a single-photon avalanche diode (SPAD). Similarly, the collection area can be increased using a large array of SPAD elements. However, several important parameters are associated with the size of the array and a SPAD element, such as the effective recovery time, output pulse width or bandwidth, and linearity, which significantly impact the sensitivity and achievable data rate.